EASTERN MOTIFS IN THE WORKS OF A.S. PUSHKIN - Shagieva, Nargis Fagimovna (Mental Enlightenment Scientific-Methodological Journal, 2025)
This article examines the influence of Eastern motifs in the works of A.S. Pushkin, highlighting their thematic, stylistic, and ideological significance. Pushkin’s fascination with the East, shaped by literary, historical, and cultural influences have been reflected in his poetry and prose through exotic imagery, oriental philosophy, and depictions of Eastern traditions. The article describes key works such as The Fountain of Bakhchisarai, The Prisoner of the Caucasus, and Ruslan and Lyudmila, analyzing how Eastern aesthetics and narratives contribute to the development of Pushkin’s artistic vision. Special attention is given to the poet’s perception of the East, its romanticized representation, and its role in shaping Russian literary Orientalism. The research also addresses Pushkin’s adaptation of Eastern themes within the broader context of 19th-century Russian literature.